PENGARUH PENGAMPUNAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Robby Alexander Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
One of the objectives of tax amnesty is to increase taxpayer compliance. This research empirically analyzes the effect of tax amnesty on taxpayer compliance in Indonesia. The data were collected from 34 provinces between 2015 and 2019. To analyze cross-provinces panel data of 34 provinces from 2015 to 2019, we used a fixed effect model (FEM). The findings showed tax amnesty has no effect on taxpayer compliance. Another finding is tax knowledge as measured by the level of education has a positive influence on taxpayer compliance and is statistically significant. And finally, we suggest the government consider carefully when re-implementing the tax amnesty. We also provide several recommendations to significantly increase taxpayer compliance.